Application of 4A Concept in Bogor Botanical Garden Tourism Development Strategy - Yohana, Yohana; Nugraha, Rizki Nurul (West Science Social and Humanities Studies, 2024)
Indonesia is very rich in natural tourism potential (ecotourism), one of which is natural tourism in conservation areas. Bogor Botanical Garden is an ex-situ conservation area that has long been used by the wider community as a tourist attraction and in many countries, Bogor Botanical Garden is one of the most popular tourist destinations because it presents a panoramic view of natural landscape architecture. The research entitled "Application of the 4A Concept in the Development of Bogor Botanical Garden Tourism" focuses on the 4A concept, namely Attraction, Accessibility, Amenities, and Ancillary services. This type of research is qualitative, using qualitative descriptive analysis methods. Data collection is carried out by means of field observation, interviews, and literature studies. SWOT analysis was also used in this study, to identify the strengths and opportunities of Bogor Botanical Garden, and determine strategies to reduce weaknesses and challenges. The results showed changes in the management system of Bogor Botanical Garden. By analyzing the 4A concept, this study seeks to provide recommendations for the right development strategy for KRB, so that it can develop better and the vision of Bogor Botanical Garden can be achieved.